Radiation diligence must continue when using newer fluoroscopes. Issue 5 (9th November 2021) - Balter, Stephen
Key Points: The ratio between patient and staff irradiation for a given procedure varies between different fluoroscopes. Operator irradiation is also affected by the way that the fluoroscope is clinically used. Diligence in monitoring of both patient and staff irradiation are still required when using newer fluoroscopes.